Bilateral matching decision-making in property trading platform: a method considering intermediary moral hazard - Wang, Rui; Zuo, Wenjin (International Journal of Strategic Property Management, 2023)
Effective method of bilateral matching decision-making could drive the property transaction market more dynamic and healthier. In the property trade process, once intermediaries are conscientious, the portrait of matching parties are clearly described, a reasonable and satisfactory result can be got. However, the intermediary moral hazard and the loss of the description about the characteristics of matching parties can affect the matching result. By developing a method for a property transaction platform, this paper proposes a novel approach that considering intermediary moral hazard to improve matching efficiency. A mathematical model of intermediary moral hazard is performed, and then the price and other evaluation indicators of sellers and buyers are described by five different types of value forms. A multi-objective bilateral matching decision-making model that “minimizes the intermediary moral hazard in the case of the maximum benefits of the matching parties” is constructed and solved by the dictionary order method. A real case study of property trade platform is presented to illustrate how the proposed approach could be applied in practice. The results of this research indicate that the proposed approach is a useful tool for matching sellers and buyers under the intermediary moral hazard and has substantial practical application.